AN EXPLORATION OF ETHNIC HUMOR, POLYSEMY, AND CULTURAL STEREOTYPES - Kendjaeva Zemfira (Bright Mind Publishing, 2025)
This article investigates the interplay between polysemy and cultural stereotypes in ethnic humor, focusing on English language anecdotes that exploit ambiguous metaphors to activate in group/out group schemas. Drawing on cognitive linguistic theories of polysemy (Pustejovsky, 1995), metaphor (Dynel, 2006; Attardo, 2015) and humor processing (Raskin, 1985; Davis & Hofmann, 2023), alongside empirical studies of ethnic humor (Gogová, 2016; Yus, 2008), it examines how multifaceted metaphors facilitate rapid stereotype activation, exemplified by the “stingy Scot” trope. Through qualitative analysis of joke corpora, the study reveals mechanisms by which semantic ambiguity and cultural framing reinforce biases, offering insights for mitigative interventions in intercultural communication.
Keywords: Polysemy; Cultural stereotypes; Ethnic humor; Ambiguous metaphor; In group/out group schemas; Scots stereotype; Cognitive linguistics; Humor studies.